Chloroplast dehydroascorbate reductase and glutathione cooperatively determine the capacity for ascorbate accumulation under photooxidative stress conditions. (8th February 2023) - Hamada, Akane; Tanaka, Yasuhiro; Ishikawa, Takahiro; Maruta, Takanori
SUMMARY: Ascorbate is an indispensable redox buffer essential for plant growth and stress acclimation. Its oxidized form, dehydroascorbate (DHA), undergoes rapid degradation unless it is recycled back into ascorbate by glutathione (GSH)‐dependent enzymatic or non‐enzymatic reactions, with the enzymatic reactions catalyzed by dehydroascorbate reductases (DHARs). Our recent study utilizing an Arabidopsis quadruple mutant (∆ dhar pad2 ), which lacks all three DHARs (∆ dhar ) and is deficient in GSH ( pad2 ), has posited that these GSH‐dependent reactions operate in a complementary manner, enabling a high accumulation of ascorbate under high‐light stress. However, as Arabidopsis DHAR functions in the cytosol or chloroplasts, it remained unclear which isoform played a more significant role in cooperation with GSH‐dependent non‐enzymatic reactions. To further comprehend the intricate network of ascorbate recycling systems in plants, we generated mutant lines lacking cytosolic DHAR1/2 or chloroplastic DHAR3, or both, in another GSH‐deficient background ( cad2 ). A comprehensive comparison of ascorbate profiles in these mutants under conditions of photooxidative stress induced by various light intensities or methyl viologen unequivocally demonstrated that chloroplastic DHAR3, but not cytosolic isoforms, works in concert with GSH to accumulate ascorbate. Our findings further illustrate that imbalances between stress intensity and recycling capacity significantly impact ascorbate pool size and tolerance to photooxidative stress. Additionally, it was found that the absence of DHARs and GSH deficiency do not impede ascorbate biosynthesis, at least in terms of transcription or activity of biosynthetic enzymes. This study provides insights into the robustness of ascorbate recycling. Significance Statement: Ascorbate recycling consists of complex and redundant systems, and the whole picture is not fully understood. Here, we show that cooperation between chloroplast dehydroascorbate reductase and glutathione enables the high accumulation of ascorbate under photooxidative stress to protect cells from oxidative damage.